Sistem Pemujaan Soroh Nyuwung Di Desa Abianbase Kabupaten Gianyar: (Kajian Teologi Hindu) - Harsananda, Hari; Yoga Segara, I Nyoman; Wastawa, I Wayan (Jayapangus Press, 2025)
This research discusses one Soroh (lineage group) in Abianbase Village, Gianyar Regency, which has a different worship system compared to other Sorohs in Bali. Therefore, this study aims to map the subsystems that form part of a complete worship system. These include the beliefs held by Soroh Nyuwung, the presence of the Dukuh figure as a religious leader for Soroh Nyuwung, and the structuring of sacred places that serve as media for worship for Soroh Nyuwung in Abianbase Village, Gianyar Regency. This research is qualitative with an ethnographic approach. Data was obtained through observation at the location, interviews with religious leaders of Soroh Nyuwung, and document studies in the form of copies of the Soroh Nyuwung inscription which contains the rules of life for Soroh Nyuwung. The data was analyzed through data reduction, classification, and display processes, as well as conclusion drawing and verification, ultimately being presented descriptively and narratively. The research results show that the Soroh Nyuwung worship system contains three subsystems: belief in Hyang Sinuhun Kidul, who for Soroh Nyuwung is closely affiliated with Bhatara Brahma and is believed to be the ancestor who created the descendants of Soroh Nyuwung. Furthermore, there is the existence of a figure titled Dukuh as the sole leader in every ceremony. Dukuhs are stratified into two types: Dukuh Pengarep and Dukuh Pengabih. There are also sacred places or places of worship for Sang Hyang Sinuhun Kidul called Gedong Sinapa, located in Pura Panti and Sanggah Pamerajan, which are known to have existed since ancient Balinese times. These three subsystems synergize to form a rigid system, creating a systemic pattern of worship by Soroh Nyuwung towards the entity they sanctify, namely Sang Hyang Sinuhun Kidul.